Efficacy of Preoperative Topical Testosterone Therapy for Micro Phallic Hypospadias: Experience in Dhaka Shishu (Children) Hospital - Ali, Md Ayub; Md Hasanuzzaman, -; Palit, Paritosh Kumar (Dhaka Shishu (Children) Hospital Journal, 2021)
Introduction: Surgical correction of genital defect was formally proposed when the size of the penis is sufficient to permit easy surgical repair. Delaying surgical repair until the phallus is of suitable size or pretreatment with hormones is recommended. In micro phallic hypospadias, temporary stimulation with testosterone either topical or parenteral to enlarge the penile size has been reported. Objective: Aim of this study was to evaluate the efficacy of preoperative topical testosterone therapy in micro phallic hypospadias patients. Methods: This retrospective study was carried out in the division of pediatric surgery, Dhaka Shishu (Children) Hospital. Hospital records of patients with micro phallic hypospadias from July 2015 to December 2017 were analyzed. All patients received testosterone cream 3 times daily for three weeks. Alteration of penile length, glans width and the adverse effects of testosterone therapy were recorded. Data were analyzed by using SPSS version 22. Results: Total 35 patients received topical testosterone therapy during the study period. The mean penile length of penis was changed from 2.71±0.49 cm to 3.46±0.26 cm, which was statistically significant (p<0.05). The mean glans width was changed from 1.13±0.18 cm to 1.29±0.13 cm, which was statistically significant (p<0.05). Minor adverse effects were noted like pubic hair, genital pigmentation, and dermatitis. Conclusion: Significant penile growth was observed with minor adverse effects after using topical testosterone therapy. DS (Child) H J 2018; 34(1) : 22-25